Defectiveness in tender document / Muhammad Alif Syahmi Ahmad Fauzi and Kharizam Ismail - Ahmad Fauzi, Muhammad Alif Syahmi; Ismail, Kharizam (2019)
Defectiveness in the tender document is an error happen during the preparation of tender document by quantity surveyor for construction projects. Defectiveness term in this research is referring to imperfection, incomplete or errors. The tender document is actually a document that contains all information about the proposed project and uses to estimate the sum for the project and all the works in the project. However, there also have many problems that pertaining in defectiveness of tender documents such as overrun cost of the building and problem in preparing tender documents such as errors in specifications are design errors, poor coordination between design disciplines, missing information, abbreviation and symbol errors. Therefore, the aim of the research is to recommend a checklist for an inclusive tender document. The objective of this research is to identify the factors causes of defectiveness in the tender document. To achieve the objectives, the data is collected through a questionnaire survey which involved 118 Quantity Surveyor (QS) from consultants and contractor organization at Petaling Jaya. The outcome of the research is expected to guard all quantity surveyor ether in consultant or contractor to produce an inclusive of tender document.